European Society of Contact Dermatitis guideline for diagnostic patch testing - recommendations on best practice - Johansen, Jeanne D.; Aalto-Korte, Kristiina; Agner, Tove; Andersen, Klaus E.; Bircher, Andreas; Bruze, Magnus; Cannavo, Alicia; Gimenez-Arnau, Ana; Goncalo, Margarida; Goossens, An; John, Swen M.; Liden, Carola; et al. (Contact Dermatitis, 2015)
The present guideline summarizes all aspects of patch testing for the diagnosis of contact allergy in patients suspected of suffering, or having been suffering, from allergic contact dermatitis or other delayed-type hypersensitivity skin and mucosal conditions. Sections with brief descriptions and discussions of different pertinent topics are followed by a highlighted short practical recommendation. Topics comprise, after an introduction with important definitions, materials, technique, modifications of epicutaneous testing, individual factors influencing the patch test outcome or necessitating special considerations, children, patients with occupational contact dermatitis and drug eruptions as special groups, patch testing of materials brought in by the patient, adverse effects of patch testing, and the final evaluation and patient counselling based on this judgement. Finally, short reference is made to aspects of (continuing) medical education and to electronic collection of data for epidemiological surveillance.
EVALuna2:5523